Optimal Planning Target Volume Margins for Elective Pelvic Lymphatic Radiotherapy in High-Risk Prostate Cancer Patients. (7th March 2013) - Hinton, Benjamin K.; Fiveash, John B.; Wu, Xingen; Dobelbower, Michael C.; Kim, Robert Y.; Jacob, Rojymon
Abstract : Purpose . High-risk prostate cancer patients often receive radiotherapy (RT) to pelvic lymphatics (PLs). The aim of this study was to determine the safety margin around clinical target volume for PL (PL-CTV) to construct planning target volume for PL (PL-PTV) and for planning elective PL irradiation. Methods and Materials . Six patients who received RT to PL as part of prostate cancer treatment were identified. To determine average daily shifts of PL, the right and left IVs were contoured at 3 predetermined slices on the daily MV scans and their daily shifts were measured at these 3 levels using a measuring tool. Results . A total of 1, 932 observations were made. Daily shifts of IV were random in distribution, and the largest observed shift was 13.6 mm in lateral and 15.4 mm in AP directions. The mean lateral and AP shifts of IV were 2.1 mm (±2.2) and 3.5 mm (±2.7), respectively. The data suggest that AP and lateral margins of 8.9 mm and 6.5 mm are necessary. Conclusions . With daily alignment to the prostate, we recommend an additional PL-CTV to PL-PTV conversion margin of 9 mm (AP) and 7 mm (lateral) to account for daily displacement of PL relative to the prostate.